Skenario Pengembangan Fasilitas Sistem Pengolahan Sampah Dengan Pendekatan Cost Benefit Analysis Di Kelurahan Kedamaian Kota Bandar Lampung - Arlina Phelia; Ria Oktaviani Sinia (Fakultas Teknik, 2021)
Bandar Lampung City is part of the major city of Lampung province. The problem that arises in Bandar Lampung City is solid waste management. The amount of solid waste in Bandar Lampung City reaches 1000 tons/day. One of the district of Bandar Lampung named Kedamaian district still uses the old method (collecting-transport-throw) in solid waste management, which causes the load of waste to accumulate in the landfill. The constraints encountered this time are the absence of sorting locations and limited land. Kedamaian district needs to develop waste treatment facilities, an approach based on Cost Benefit Analysis (CBA). The results show from the analysis that BCR in the scenario A 1 is 0.85 with NPV - Rp. 72.968.828. the activity in the existing conditions can still be carried out, but the waste reduction has not been maximized to the TPS (Container). Scenario B, NPV is Rp. 95.319.338 and BCR is 1.13, which value of BCR is 1. This indicates that a waste processing facility in the Kedamaian District is suitable to operate with TPS-3R. The results of scenario B are obtained by increasing the effectiveness of processing facilities to 100% by 2025. In 2025, with the implementation of the TPS-3R obtained, BCR is 1.20 with NPV is Rp. 218.447.621.